Oxygen Saturation in Neonates After Birth in Rural Hospital - Taksande, Amar; Meshram, Rewat; Lohakare, Amol; Purandare, Sadhana; Kommawar, Ankush (Cardiology and Cardiovascular Medicine, 2017)
Background: Pulse oximetry is a noninvasive test for quantification of hypoxemia. It is a simple bedside test to determine the amount of oxygen in a baby's blood and use for early detection of critical congenital heart disease (CCHD). Aim: To analyze the influence of birth weight, gestational age, mode of delivery and gender, on levels of SpO2 in healthy newborns. Methods: Within first 6 hours of life, pulse oximetry was performed on clinically normal newborns. Echocardiography was performed, if oxygen saturation (SpO2) was below 90%. Inclusion criteria: Newborns who were admitted in postnatal ward & NICU. Exclusion criteria: Out born babies and babies with a prenatal diagnosis of duct dependent circulation. SpO2 were performed using a Massimo Single Extraction Technology (SET) handheld pulse oximeter with a neonatal reusable Nellcor SpO2 sensor OXI-A/N probe. For each newborn, SpO2 was measured by trained social worker of the newborn within the first 6 hours of life. The probe was held manually to the sole of the foot. Results: A total of 6101 neonates were born at the hospital during the period of January 2013 to December 2014 and registered in the CCHD screening project. For 68 neonates (1.1%), the first SpO2 was <95% and they were not included in the further analyses. 1958 neonates with weight less than 2.5 kg were excluded from the study. A total of 4075 neonates (1961 boys and 2114 girls) fulfilled the criteria for inclusion in the final analyses. The mean birth weight of the neonates was 2.81±0.27 Kg and the mean GA was 38.64±1.29 weeks. SpO2 was not related to GA when analyzed by one-way ANOVA (F: 0.88; P>0.01). No statistical significant difference in SpO2 was found in children born by caesarean section (98.62±1.20) than in those delivered vaginally (98.62±1.17). <br